Jon Fosses "Namnet" - en lesning - Monika, Grossman (Folia Scandinavica Posnaniensia, 2007)
Jon Fosse is perhaps the most popular contemporary Norwegian playwright today, often being compared to Henrik Ibsen. This article analyses one of his most famous and frequently staged dramas, “The Name”. Reference is made to Peter Szondi’s definition of classical drama as interpersonal relationships in the present, but it is used to show that a negation of the above is the underlying principle of Fosse’s plays, including “The Name”. Fosse seems to be of the opinion that interpersonal relationships in the modern world are barely possible. An analysis of “The Name” is done to illustrate this thesis. Major importance has been given to the language, with its typical features such as repetitions, aborted sentences and pauses. The author concludes that the extraordinary characteristics of Fosse’s language are the most prominent and idiosyncratic element of his rather traditionally constructed plays and, hence, a key to his growing popularity outside Norway.